Waterborne epoxy emulsified asphalt high-skid-resistance thin layer structure and construction method thereof

By chemically bonding the water-based epoxy emulsified asphalt waterproof bonding layer with the high anti-skid thin layer and using a single-size aggregate design, the problem of insufficient anti-skid properties of asphalt pavement is solved, achieving efficient and environmentally friendly anti-skid thin layer construction and improving pavement durability and safety.

CN120925383AActive Publication Date: 2025-11-11GUANGXI COMM PLANNING SURVEYING & DESIGNING INST

Patent Information

Application Number
CN202511467845.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-15
Publication Date
2025-11-11
Estimated Expiration
2045-10-15

AI Technical Summary

Technical Problem

In existing technologies, the design of high skid resistance thin-layer structure of waterborne epoxy emulsified asphalt is insufficient, failing to effectively improve the skid resistance and durability of asphalt pavement, and the construction process fails to fully utilize the material properties.

Method used

It adopts a two-layer structure design. The lower layer is a water-based epoxy emulsified asphalt waterproof adhesive layer, and the upper layer is a high anti-slip thin layer. The epoxy resin forms chemical bonds through a three-dimensional cross-linking network, combined with single-size wear-resistant aggregates to form a macroscopic structural depth. It adopts a normal temperature construction process.

Benefits of technology

It significantly improves the skid resistance and durability of asphalt pavement, solves problems such as rutting, cracking, and aging, and is environmentally friendly and efficient in construction, meeting the needs of green road construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120925383A_ABST
    Figure CN120925383A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of asphalt pavement preventability, in particular to a water-based epoxy emulsified asphalt high-skid-resistance thin layer structure and a construction method thereof, and the structure sequentially comprises a water-based epoxy emulsified asphalt waterproof bonding layer and a water-based epoxy emulsified asphalt high-skid-resistance thin layer from bottom to top. And the waterproof bonding layer is formed by mixing emulsified asphalt and water-borne epoxy resin, demulsifying and curing. The high-skid-resistance thin layer is formed by mixing, paving, rolling and curing a wear-resistant aggregate and a water-based epoxy emulsified asphalt cementing material, the cementing material is demulsified and cured to form a three-dimensional cross-linked network structure, and the wear-resistant aggregate is embedded into the cementing material in a point contact manner and partially protrudes out of the surface of the cementing material. Compared with the prior art, the two-layer structure forms chemical bonding and synergistic enhancement through a three-dimensional cross-linked network of epoxy resin, has excellent surface skid resistance, water stability and durability, can effectively solve the problem of insufficient skid resistance of an asphalt pavement, remarkably improves the driving safety, and adopts normal-temperature construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of asphalt pavement preventive technology, and in particular to a water-based epoxy emulsified asphalt high skid-resistant thin-layer structure and its construction method. Background Technology

[0002] Asphalt pavement is an important component of highway engineering. Compared with cement concrete pavement, asphalt pavement has advantages such as smooth surface, no joints, comfortable driving, low vibration, and low noise, and has therefore been widely used and is the main pavement structure in my country. However, with the increasing weight of traffic loads and the continuous upgrading of traffic volume, the early asphalt pavement has been subjected to the coupling effect of load and humid and hot environment, and has developed problems such as insufficient skid resistance, cracks, pitting, rutting, and loosening and peeling. In particular, the skid resistance problem of asphalt pavement has become one of the most common problems in the early service of asphalt pavement, which not only affects the service life of the pavement, but also makes it easier to cause vehicle driving safety hazards under rain conditions. At present, there are two main treatment methods for the above problems of asphalt pavement: (1) milling the original asphalt pavement and repaving with new asphalt mixture; (2) laying an ultra-thin overlay on the basis of the original pavement. Compared with milling and repaving, the ultra-thin overlay method is more economical and feasible. By selecting high skid-resistant aggregates and high-performance binders, low-carbon, durable, and high skid-resistant thin-layer maintenance materials can be designed.

[0003] Waterborne epoxy emulsified asphalt is a new high-performance road maintenance material that has emerged in recent years. It is mainly composed of epoxy emulsion, curing agent, and emulsified asphalt. Waterborne epoxy resin is an environmentally friendly material obtained by emulsifying epoxy resin using a specific process. It has advantages such as being pollution-free, easy to store and transport, and having good workability. When mixed with a curing agent, it can develop into a non-melting three-dimensional cross-linked network. Compared with traditional polymer latex, using waterborne epoxy resin as a modifier can significantly improve the adhesion, water stability, and high-temperature stability of asphalt, overcoming the technical deficiencies of traditional modified emulsified asphalt and thus improving the road performance of the mixture. Exploring the design and construction technology of high-skid-resistance thin-layer structures using waterborne epoxy emulsified asphalt as the binder and high-skid-resistance aggregate as the aggregate for asphalt pavements has become a research focus.

[0004] For example, Chinese patent CN114644493A discloses a high-performance waterborne epoxy-modified emulsified asphalt micro-surfacing material and its preparation method. This maintenance material uses a micro-surfacing dense gradation, with the aggregate consisting of three grades of basalt coarse aggregate (4.75~9.5mm), fine aggregate (0.075~4.75mm), and filler (<0.075mm). Waterborne epoxy emulsified asphalt is used as the binder, ultimately developing a waterborne epoxy emulsified asphalt micro-surfacing mixture with excellent wear resistance, water stability, and deformation resistance. However, because the micro-surfacing mixture has a relatively low structural depth, its anti-skid performance needs further improvement.

[0005] Chinese patent CN116399756A discloses a method for determining the effective construction time of mixed water-based epoxy emulsified asphalt. It uses a viscometer to analyze the viscosity-time curve of the water-based epoxy emulsified asphalt, dividing the curing process of the actual mixed water-based epoxy emulsified asphalt into liquid, gel, and solid states, closely corresponding the curing process to the actual construction procedures to meet the needs of efficient on-site construction organization. However, it does not cover the specific construction technology of water-based epoxy emulsified asphalt curing materials.

[0006] For example, the literature "Design and Performance Comparison of Ultra-thin Wearing Layers Based on Waterborne Epoxy Emulsified Asphalt Gradation" (Zhou Mingyu, Materials Reports, January 2024, Vol. 38, No. 24, pp. 265-272) discloses design methods for ultra-thin wearing layers of waterborne epoxy emulsified asphalt with three different gradations: AC-10, SMA-10, and UWM-10, and analyzes the influence of gradation on the performance of ultra-thin wearing layers. However, it still fails to design anti-skid thin-layer structures and construction processes based on the characteristics of waterborne epoxy emulsified asphalt binders.

[0007] It is evident that although there is considerable research on waterborne epoxy emulsified asphalt curing materials, the focus is primarily on the compact structure. There is insufficient research on the development and structural design of single-particle-size high-skid-resistance thin layers. Furthermore, the characteristics of waterborne epoxy emulsified asphalt materials have not been considered, and no key construction processes for waterborne epoxy emulsified asphalt high-skid-resistance thin layers have been proposed. Summary of the Invention

[0008] The purpose of this invention is to overcome the defects of the prior art by providing a water-based epoxy emulsified asphalt high skid-resistant thin-layer structure and its construction method. The two layers are chemically bonded through a three-dimensional cross-linked network of epoxy resin, which synergistically enhances the structure and provides excellent surface skid resistance, water stability and durability. This effectively solves the problem of insufficient skid resistance of asphalt pavement, significantly improves driving safety, and can be constructed at room temperature.

[0009] The objective of this invention can be achieved through the following technical solutions: The first aspect of this invention provides a water-based epoxy emulsified asphalt high skid-resistance thin-layer structure, the high skid-resistance thin-layer structure comprising, from bottom to top: Waterborne epoxy emulsified asphalt waterproof bonding layer is formed by mixing emulsified asphalt and waterborne epoxy resin and then demulsifying and curing it. It is used to seal the original asphalt pavement and provide interlayer bonding. A waterborne epoxy emulsified asphalt high anti-skid thin layer is formed by mixing, spreading, rolling and curing abrasion-resistant aggregate and waterborne epoxy emulsified asphalt binder. The waterborne epoxy emulsified asphalt binder is made by mixing emulsified asphalt and waterborne epoxy resin. After demulsification and curing, it forms a three-dimensional cross-linked network structure. The abrasion-resistant aggregate is embedded in the waterborne epoxy emulsified asphalt binder in a point contact form and partially protrudes from the surface of the waterborne epoxy emulsified asphalt binder, together forming a waterborne epoxy emulsified asphalt high anti-skid thin layer with macroscopic structural depth. The waterborne epoxy emulsified asphalt waterproof adhesive layer and the waterborne epoxy emulsified asphalt high anti-skid thin layer are chemically bonded through a three-dimensional cross-linking network of epoxy resin.

[0010] Furthermore, the waterborne epoxy emulsified asphalt waterproof adhesive layer comprises the following components in the following mass ratio: 100 parts emulsified asphalt and 3-6 parts waterborne epoxy resin. The emulsified asphalt used is a cationic slow-cracking emulsified asphalt with a solid content of 50% to 60%. The waterborne epoxy resin is a two-component epoxy resin, wherein component A is an epoxy emulsion and component B is a curing agent.

[0011] Furthermore, the waterborne epoxy emulsified asphalt high anti-skid thin layer comprises the following components in the following mass ratios: 100 parts of high anti-skid aggregate with a single particle size of 3mm~5mm, 10~14 parts of water-based epoxy emulsified asphalt binder, 1~3 parts of cement admixture, and 2~6 parts of water for wetting and adjusting consistency.

[0012] Furthermore, the application rate of the water-based epoxy emulsified asphalt waterproof adhesive layer is 0.6~0.8 kg / m³. 2 ; The thickness of the water-based epoxy emulsified asphalt high anti-skid thin layer is 5mm~12mm.

[0013] Furthermore, the waterborne epoxy emulsified asphalt binder in the waterborne epoxy emulsified asphalt high anti-skid thin layer comprises the following components in the following mass ratio: 100 parts emulsified asphalt and 6-30 parts waterborne epoxy resin. The emulsified asphalt is a cationic slow-cracking emulsified asphalt with a solid content of not less than 60%. The waterborne epoxy resin is a two-component epoxy resin, wherein component A is an epoxy emulsion and component B is a curing agent; The cement admixture is P.O42.5, and the water used for wetting and consistency adjustment is tap water.

[0014] Furthermore, the wear-resistant aggregate includes basalt, diabase, steel slag, and ceramsite with a single particle size range of 3-5 mm.

[0015] A second aspect of the present invention provides a construction method for a water-based epoxy emulsified asphalt high skid-resistance thin-layer structure as described above, characterized by comprising the following steps: S1. Clean and dry the original asphalt pavement, and treat potholes, craters, and cracks larger than 5mm. S2. Mix the two-component waterborne epoxy resin in proportion and add it into the emulsified asphalt tank of the sprayer. Turn on the internal circulation to make the components evenly mixed. Then spray it onto the treated road surface in a controlled amount to form a waterborne epoxy emulsified asphalt waterproof bonding layer. S3. Waterborne epoxy resin and emulsified asphalt are premixed in a slurry sealer to form a binder, which is then mixed with single-size wear-resistant aggregate, cement, and water, and then spread on the waterborne epoxy emulsified asphalt waterproof bonding layer. S4. After the binder in the paving layer in S3 has broken emulsion and formed initial bond strength, the thin layer is rolled by static pressure to make the aggregate stably embedded in the binder and form a uniform surface. S5. After the thin layer in S4 has been rolled, it is sealed and cured. Traffic is opened after the water-based epoxy resin has fully cured to form a three-dimensional cross-linked network structure and the strength meets the requirements.

[0016] Furthermore, in S2 and S3, the mixing of waterborne epoxy resin and emulsified asphalt is achieved by opening the internal circulation in the tank of the construction machinery for at least 10 minutes, the speed of the sprayer is controlled at 2-4 km / h, and the speed of the paver is controlled at 1.5-3.0 km / h.

[0017] Furthermore, in S4, when the temperature is between 5-25℃, the compaction time is 3-4 hours; When the temperature is above 25℃, the compaction time is 1-2 hours; During the compaction process, a double-drum roller with a capacity of no more than 13 tons is used to perform 1-2 static compactions at a speed of 2-4 km / h.

[0018] Furthermore, in S5, the curing time is determined based on the ambient temperature to ensure that the waterborne epoxy resin is fully cross-linked and cured to achieve the design strength. When the temperature is between 5-25℃, the health regimen should last for 2-3 hours. When the temperature is above 25℃, the health regimen should last for 1-2 hours.

[0019] The core mechanism of the waterborne epoxy emulsified asphalt high-skid-resistance thin-layer structure and its construction method of this invention lies in achieving a comprehensive improvement in interlayer bond strength, surface skid resistance, and durability through the synergistic effect of materials science and unique structural design. Its mechanism is mainly reflected in three levels: chemical modification at the material level, physical interlocking at the structural level, and time-sequence control at the process level. At the material level, the key technology lies in using waterborne epoxy resin-modified emulsified asphalt as the bonding system for the entire structure. Waterborne epoxy resin is a two-component thermosetting material. After its component A (epoxy emulsion) and component B (curing agent) are mixed, a cross-linking curing reaction occurs in an aqueous environment, forming a dense three-dimensional interpenetrating network structure. This network interpenetrates and synergistically interacts with the asphalt phase formed after the emulsified asphalt demulsifies, significantly improving the bulk strength, adhesion, and high-temperature stability of the binder, overcoming the shortcomings of weak adhesion and poor weather resistance of ordinary emulsified asphalt, while maintaining the convenience of room-temperature construction due to the characteristics of the waterborne system. At the structural level, the design employs a composite structure of a waterproof adhesive layer and a high-skid-resistance functional layer. The lower waterproof adhesive layer not only seals the original road surface and prevents water infiltration, but its internal epoxy resin network also forms a chemical bond with the epoxy system in the upper functional layer, achieving a high-strength organic connection between the two layers and avoiding the risk of interlayer delamination. The upper high-skid-resistance thin layer innovatively uses wear-resistant aggregates of a single particle size. These aggregate particles are distributed in a random point-contact manner during mixing and paving, and through the compaction process, some of their sharp edges are stably embedded in the demulsified epoxy-asphalt composite binder below, while other sharp edges protrude from the surface, thus forming a macroscopic texture depth with high and uniform macro-roughness. This structure of the invention ensures excellent mechanical engagement and drainage path between the tire and the road surface, greatly improving skid resistance, especially under rainy driving conditions. At the process level, the construction method is designed to closely match the material's reaction mechanism. The curing of epoxy resin is a time- and temperature-dependent chemical reaction process, therefore, the timing control of key processes during construction is crucial. From the application of the waterproof adhesive layer and the laying of the high anti-slip thin layer, to the control of the waiting time for compaction after demulsification, and finally the curing time determined according to the ambient temperature, the design of this series of process parameters is all to ensure that the epoxy resin has enough time to complete its cross-linking and curing process, so that the excellent performance of the material can be fully developed.

[0020] Compared with the prior art, the present invention has the following beneficial effects: This invention uses water-based epoxy emulsified asphalt as the waterproof bonding layer, exhibiting excellent waterproofing and bonding performance, effectively preventing seepage and bonding the surface layer. The anti-skid thin layer uses high-skid-resistance aggregate of a single particle size. The resulting curing layer possesses excellent surface texture, water stability, deformation resistance, and durability, effectively addressing maintenance problems such as rutting, insufficient skid resistance, cracking, and aging in asphalt pavements, significantly improving the skid resistance and driving safety of asphalt pavements. Furthermore, it utilizes ambient temperature construction, eliminating the need for large-scale paving equipment, thus saving energy and being environmentally friendly, aligning with current green road construction concepts. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the construction method for the waterborne epoxy emulsified asphalt high skid-resistant thin-layer structure in Example 1; Figure 2 This is a schematic diagram of the high skid resistance thin-layer structure of waterborne epoxy emulsified asphalt in the embodiment.

[0022] In the diagram: 1. 1cm water-based epoxy emulsified asphalt high skid resistance thin layer; 2. water-based epoxy emulsified asphalt waterproof bonding layer; 3. original pavement asphalt mixture layer. Detailed Implementation

[0023] Overall, the water-based epoxy emulsified asphalt high-skid-resistance thin-layer structure and its construction process in this invention, with the maintenance structure consisting of, from bottom to top, the treated original asphalt pavement, a water-based epoxy emulsified asphalt waterproof bonding layer, and a water-based epoxy emulsified asphalt high-skid-resistance thin layer. The waterproof bonding layer consists of 100 parts emulsified asphalt and 3-6 parts water-based epoxy resin, with a spraying rate of 0.6-0.8 kg / m³. 2 The emulsified asphalt used is cationic emulsified asphalt with a solid content of 50%~60%. The waterborne epoxy resin is a two-component compound (component A is epoxy emulsion, and component B is curing agent). The high-skid-resistance thin layer of waterborne epoxy emulsified asphalt consists of 100 parts of high-skid-resistance aggregate (basalt, diabase, steel slag, ceramsite) with a single particle size of 3mm~5mm, 10~14 parts of waterborne epoxy emulsified asphalt, 1~3 parts of cement admixture, and 2~6 parts of water for wetting and consistency adjustment, with a laying thickness of 5mm~12mm. The waterborne epoxy emulsified asphalt binder used in the high-skid-resistance thin layer of waterborne epoxy emulsified asphalt consists of 100 parts of emulsified asphalt and 6~30 parts of waterborne epoxy resin. The emulsified asphalt is cationic emulsified asphalt with a solid content of not less than 60%. The waterborne epoxy resin has the same two-component system as the waterproof bonding layer, and the water used is tap water.

[0024] The construction process of waterborne epoxy emulsified asphalt mixture in this invention is as follows: surface cleaning → application of waterborne epoxy emulsified asphalt waterproof bonding material → mixing and paving of the mixture → compaction of the mixture → curing of a high-skid-resistance thin layer, ultimately obtaining a waterborne epoxy emulsified asphalt high-skid-resistance thin layer. This anti-skid thin layer uses waterborne epoxy emulsified asphalt as the binder, which forms a high-performance epoxy-modified asphalt binder after demulsification and curing. It also uses high-skid-resistance aggregates of a single particle size. The resulting curing layer has excellent surface texture, water stability, deformation resistance, and durability. It can solve maintenance problems such as rutting, insufficient skid resistance, cracking, and aging of asphalt pavements, significantly improving the skid resistance and driving safety of asphalt pavements. It is an environmentally friendly new material for rapid, room-temperature curing of asphalt pavements.

[0025] The specific construction process includes the following steps: (1) Treatment of the original road surface: Use a soft broom or vacuum cleaner to clean the bridge surface of dust and debris. For areas with water accumulation, use a hot blower and a special baking lamp to dry them to ensure that the working surface is dry. Treat the original road surface in advance for potholes, ridges, and cracks larger than 5mm.

[0026] (2) Waterproof bonding layer application: Weigh waterborne epoxy resin components A and B into a container according to the specified mass ratio, and stir with a handheld electric mixer for 2-3 minutes to ensure thorough mixing; add the waterborne epoxy resin mixture into the emulsified asphalt tank of the sprayer truck according to the specified ratio, and turn on the internal circulation for at least 10 minutes to ensure uniform mixing of the waterborne epoxy resin and emulsified asphalt; use a sprayer truck to apply the waterborne epoxy emulsified asphalt waterproof bonding layer, controlling the speed of the sprayer truck to be 2-4 km / h at a constant speed, and controlling the spraying amount to be 0.6-0.8 kg / m³. 2 .

[0027] (3) Slurry mixture paving: Slurry seal truck is used for on-site mixing and construction. First, emulsified asphalt, 3-5mm high anti-skid aggregate, cement and water are loaded into the corresponding storage tanks of the slurry seal truck at the material yard or construction site. Then, waterborne epoxy resin component A and component B are weighed into the container according to the ratio and stirred with a hand-held electric mixer for 2-3 minutes to ensure that they are fully mixed. The waterborne epoxy resin mixture is added to the emulsified asphalt storage tank of the slurry seal truck according to the designed dosage, and the internal circulation is turned on for at least 10 minutes to ensure that the waterborne epoxy resin and emulsified asphalt are evenly mixed. After the discharge amount and paving height of each material of the slurry seal truck are marked on-site, the paving truck is started and paved at a speed of 1.5-3.0 km / h according to the marked guide line or the lane line as a reference line to obtain a waterborne epoxy emulsified asphalt high anti-skid thin layer before curing.

[0028] (4) Compaction of mixture: After the water-based epoxy emulsified asphalt high skid resistance thin layer is laid, it needs to be compacted after the binder breaks down. The time from the completion of paving to the start of compaction is the waiting time. When the temperature is 5~25℃, the waiting time is 3~4h; when the temperature is above 25℃, the waiting time is 1~2h. After the compaction time is reached, a double steel drum roller with a capacity of less than 13 tons is used to compact the mixture in a static pressure manner at a speed of 2~4km / h and 1~2 times.

[0029] (5) Curing of high skid-resistant thin layer: After compaction, curing is carried out to further improve the strength of the skid-resistant thin layer. When the temperature is 5~25℃, the curing time is 2~3 hours; when the temperature is above 25℃, the curing time is 1~2 hours; after curing, traffic can be opened to obtain water-based epoxy emulsified asphalt high skid-resistant thin layer. The construction process is as follows: Figure 1 As shown.

[0030] The construction temperature of the water-based epoxy emulsified asphalt waterproof bonding layer and its high anti-skid thin layer should be kept above 5℃. After the high anti-skid thin layer is constructed, it should be ensured that there is no rain within 24 hours. At the same time, construction is prohibited on rainy days, excessively wet or waterlogged roads.

[0031] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. Any preparation methods, materials, structures, or compositional ratios not explicitly described in this technical solution are considered common technical features disclosed in the prior art.

[0032] Example 1 This example selects the construction process of water-based epoxy emulsified asphalt high skid-resistant thin layer on the Guangxi Wuxu Airport to Datang Expressway.

[0033] I. Water-based epoxy emulsified asphalt high skid-resistance thin-layer paving structure The water-based epoxy emulsified asphalt high-skid-resistance thin layer was constructed at kilometer marker 263 on the southbound lane of the Wuwei Airport to Datang Expressway. The construction surface was 7.5 meters wide, with two lanes, and a paving length of approximately 800 meters. The waterproof bonding layer and high-skid-resistance thin layer covered an area of ​​6000 square meters. 2 Left and right, water-based epoxy emulsified asphalt high skid-resistant thin-layer structure design, such as Figure 2 As shown. The core of this embodiment is the paving of the first and second structural layers; the third structural layer is paved using conventional asphalt mixture paving methods. See also... Figure 2 The first structural layer is a 1cm water-based epoxy emulsified asphalt high anti-skid thin layer 1, the second structural layer is a water-based epoxy emulsified asphalt waterproof bonding layer 2, and the third structural layer is the original road asphalt mixture layer 3.

[0034] II. Raw material inspection and mix design 1. Raw material inspection (1) Emulsified asphalt In this embodiment, the emulsified asphalt is a cationic slow-cracking emulsified asphalt. Before delivery, the emulsified asphalt should be inspected to ensure it meets the BCR type emulsified asphalt standard in the "Technical Specification for Construction of Highway Asphalt Pavement". Considering that temperature accelerates the curing of water-based epoxy resin, and that most emulsified asphalt is used immediately after production, the temperature of the emulsified asphalt during use is specified to not exceed 50℃.

[0035] (2) Waterborne epoxy resin In this embodiment, the waterborne epoxy resin is a two-component thermosetting resin, where component A is an epoxy emulsion and component B is a curing agent. Components A and B should be randomly tested, wherein component A has a solid content ≥ 50%, an epoxy value ≥ 0.20 mol / 100g, and a viscosity ≤ 200 mPa·s, and component B has a solid content ≥ 50%, an active hydrogen equivalent ≥ 200, and a viscosity ≤ 1000 mPa·s.

[0036] (3) Waterborne epoxy emulsified asphalt This embodiment of waterborne epoxy emulsified asphalt involves waterproof bonding layers and high skid-resistant thin layers. The waterborne epoxy emulsified asphalt should be tested. For waterproof bonding layers, low-dosage (3~6%) waterborne epoxy emulsified asphalt should meet the following requirements: bond strength ≥ 0.8 MPa, and the area of ​​adhesion to aggregate ≥ 2 / 3 as tested by boiling water method. For high-dosage (6~30%) waterborne epoxy emulsified asphalt for high skid-resistant thin layers, bond strength ≥ 1.5 MPa, and the area of ​​adhesion to aggregate ≥ 4 / 5 as tested by boiling water method.

[0037] (4) Aggregates and other materials The aggregate used in the high-skid-resistance thin layer of water-based epoxy emulsified asphalt is 3mm~5mm single-particle-size high-skid-resistance aggregate (basalt, diabase, steel slag, ceramsite), which falls under the category of coarse aggregate. The aggregate should be inspected before arrival at the site to ensure it meets the technical requirements for coarse aggregates in the "Technical Specification for Construction of Highway Asphalt Pavement". The cement grade is P.O42.5, and it should be dry, loose, and free of lumps, meeting the requirements of the "Technical Specification for Construction of Highway Asphalt Pavement" (JTG F40). Tap water is used for wetting and consistency adjustment.

[0038] 2. Mix design for high skid resistance thin-layer waterborne epoxy emulsified asphalt The mix design for the production of waterborne epoxy emulsified asphalt high skid-resistance thin layers was based on the micro-surfacing design specifications in the "Technical Specification for Prevention and Maintenance of Highway Asphalt Pavement" (JTG / T 5142-01). The difference lies in the addition of a compaction process during the preparation of wet tire abrasion specimens. After standard curing at 60℃, the wet tire abrasion specimens were immediately placed in an asphalt mixture rutting test molding machine for four compaction passes, followed by cooling to room temperature before testing. The preparation of load-bearing wheel sand-adhesive specimens followed the standard method. A wet tire abrasion value of 540 g / m² after 1 hour was used as the benchmark. 2The corresponding asphalt-aggregate ratio is the lower limit, with a sand adhesion value of 450g / m on the load wheel. 2 The corresponding asphalt-aggregate ratio is the upper limit, and the amount of water-based epoxy emulsified asphalt high skid-resistant thin-layer binder is finally determined.

[0039] In this embodiment, the ratio of component A to component B in the two-component waterborne epoxy resin is 1.5:1; the waterproof adhesive layer uses 3wt% low-dosage waterborne epoxy emulsified asphalt (the application rate is controlled at 0.6~0.8 kg / m³ during construction). 2 The high skid-resistant thin layer uses 10% high-dosage water-based epoxy emulsified asphalt (the total binder content is 12% of the aggregate); the aggregate uses 3~5mm single-particle-size high skid-resistant diabase aggregate, the cement content is 2wt%, the added water content is 3wt%, and the paving thickness is 7mm.

[0040] Performance verification was conducted on the water-based epoxy emulsified asphalt high skid resistance thin layer with optimal mix ratio. The results showed that the amount of sand adhered to the loaded wheel after immersion in water for 1 hour was 195 g / m². 2 The wheel rut width change rate was 1.8%, and the amount of sand adhering to the loaded wheel after 6 days of immersion in water was 298 g / m. 2 Its performance far exceeds the Class A micro-surfacing performance requirements in the "Technical Specification for Prevention and Maintenance of Asphalt Pavement on Highways" (JTG / T5142-01), exhibiting excellent water stability, anti-stripping and anti-deformation properties. III. Waterproof Adhesive Layer Application 1. Clean the work surface Clean the bridge surface thoroughly with a soft broom or vacuum cleaner to remove dust and debris. For areas with water accumulation, use a hot air blower and a special heat lamp to dry them, ensuring the work surface is dry before construction. The construction temperature of the waterproof adhesive layer should be maintained above 10℃, and construction is prohibited in rainy or foggy conditions. Furthermore, to ensure continuous construction, weather conditions should be monitored before construction to ensure there is no rain, snow, or heavy fog within 24 hours before and after construction.

[0041] 2. Preparation of waterproof adhesive materials In this embodiment, the waterproof adhesive material is a low-dosage (3%~6%) waterborne epoxy resin modified emulsified asphalt. The waterborne epoxy resin consists of epoxy emulsion component A and curing agent component B, which are added to a container at a mass ratio of 1.5:1 and stirred for 3 minutes with a handheld electric mixer to ensure thorough mixing. The waterborne epoxy resin mixture is then added to the emulsified asphalt tank of the sprayer according to the proportion, and the internal circulation is turned on for at least 10 minutes to ensure that the waterborne epoxy resin and emulsified asphalt are evenly mixed in preparation for spraying.

[0042] 3. Apply waterproof adhesive material. Before construction, tape was used to cover the road marking surface to prevent contamination. To ensure a more even application of the waterproof adhesive layer to the original road surface, an emulsified asphalt distributor was used. The distributor used a balanced nozzle to ensure the waterproof adhesive material was applied as a uniform mist. During application, the distributor maintained a constant speed of 3 km / h, and the application rate was controlled at 0.8 kg / m³. 2 Ensure the waterproof adhesive is evenly distributed across the entire width as a thin layer; any missed areas should be manually reapplied, and any excess should be scraped off promptly. After applying the waterproof adhesive, all vehicles except the material transport vehicle and pedestrians are prohibited from passing through the area.

[0043] IV. Mixing and Spreading of the Mixture 1. Equipment calibration before construction The slurry seal truck is used for on-site mixing and construction. The raw materials involved in the water-based epoxy emulsified asphalt high skid thin layer include water-based epoxy emulsified asphalt binder, 3-5mm high skid dry aggregate, cement, and water. After the raw materials are loaded into the construction machinery, the discharge volume of each storage tank is calibrated, and the relationship curves between the opening of each material gate of the slurry seal truck or the setting of the pump and the discharge volume of each material are plotted, and a calibration report is issued.

[0044] 2. Raw material loading First, at the material yard or construction site, emulsified asphalt, 3-5mm high anti-skid dry aggregate, cement, and water are respectively loaded into the corresponding storage tanks of the slurry seal truck. Then, waterborne epoxy resin component A and component B are weighed into a container at a ratio of 1.5:1 and stirred for 3 minutes with a handheld electric mixer to ensure thorough mixing. The waterborne epoxy resin mixture is then added to the emulsified asphalt storage tank of the slurry seal truck according to the designed dosage, and the internal circulation is turned on for at least 10 minutes to ensure that the waterborne epoxy resin and emulsified asphalt are evenly mixed.

[0045] 3. Mixing and spreading of the mixture Adjust the width of the paving box according to the full width of the road and mark the directional control lines; after confirming the height or opening of each material gate, start the machine, engage the mixing cylinder clutch to start the mixing shaft, and activate the auger distributor of the paving box; adjust the flow direction of the slurry on the distributor to ensure that the slurry flows evenly to both sides of the paving box; control the consistency of the slurry by adjusting the water volume, and catch and discard the slurry mixture that initially flows out with an iron shovel; when the slurry mixture is evenly distributed across the full width of the paving box, start the chassis and move forward slowly, maintaining a forward speed between 1.5 and 3 km / h; after the mixture is paved, manual leveling should be carried out immediately, paying special attention to the starting point, ending point, longitudinal joints, and areas that are too thick, too thin, or uneven; in particular, scratches caused by oversized aggregate should be quickly removed and filled; when any material on the paver is used up, all switches should be turned off immediately to allow the mixture in the mixing cylinder to be mixed evenly; check and record the remaining material, and return to the material yard or on-site material point for reloading to continue the above construction. After completing the above construction, a thin layer of water-based epoxy emulsified asphalt with high anti-skid properties is obtained before curing.

[0046] V. Compaction of the mixture Because the high skid-resistance thin layer uses water-based epoxy emulsified asphalt as the binder and the aggregate has a single particle size of 3-5mm, the binder demulsifies and the water evaporates, resulting in more pores, uneven aggregate distribution, and unstable interlocking structure, generating significant noise. Therefore, the water-based epoxy emulsified asphalt high skid-resistance thin layer needs to be compacted.

[0047] It should be noted that after the mixing and paving processes are completed, the water-based epoxy emulsified asphalt needs to break down and form a certain bond strength. The time from the completion of paving to the start of compaction is called the waiting time for compaction. When the temperature is between 5 and 25°C, the waiting time for compaction is 3 to 4 hours; when the temperature is above 25°C, the waiting time for compaction is 1 to 2 hours. To prevent the aggregate from being crushed and the mixture from shifting, after the compaction time is reached, a double-drum roller with a capacity of less than 13 tons is used for static compaction at a speed of 2 to 4 km / h and 1 to 2 passes. In this embodiment, the specific compaction parameters used are: a speed of 3 km / h and 2 passes.

[0048] Considering that water-based epoxy emulsified asphalt mixtures are prone to sticking to the rollers, a mist of water mixed with surfactants or salad oil can be sprayed onto the steel rollers as a release agent during compaction. Diesel fuel is strictly prohibited. Roll continuously and evenly in sequence, with adjacent compaction strips overlapping by 1 / 3 of the roller width. During compaction, the roller must not turn or turn around on the pavement layer. The roller must be slowed down when starting and stopping, and sudden braking is not allowed.

[0049] VI. Health Preservation The formation process of high-skid-resistance thin-layer waterborne epoxy emulsified asphalt involves the demulsification and coagulation of the binder and the curing of the modifier, with its strength increasing continuously over time. When the strength is insufficient, to prevent damage to the high-skid-resistance thin layer from vehicle loads, traffic must be closed after compaction for road surface curing. The curing time is related to the curing temperature conditions, and the curing time is selected according to the temperature for the curing maintenance stage. It should be noted that when the temperature is between 5 and 25°C, the curing time is 2 to 3 hours; when the temperature is above 25°C, the curing time is 1 to 2 hours. The standard for opening traffic is that when the road surface is completely dry, the aggregate can be felt with a finger, exhibiting a clear cohesive force, and the coarse aggregate particles on the surface do not slip when pushed. Traffic can then be opened, resulting in a high-skid-resistance thin-layer waterborne epoxy emulsified asphalt. In this embodiment, the specific curing parameters used are: temperature 30°C, curing time 1 hour.

[0050] VII. Post-construction road performance testing To determine whether the waterborne epoxy emulsified asphalt high-skid-resistance thin layer performs well in road use, its appearance and performance need to be tested. The test indicators and results are shown in Table 1. The waterborne epoxy emulsified asphalt high-skid-resistance thin layer exhibits excellent road performance, especially in terms of skid resistance.

[0051] Table 1. Detection Indicators and Results

[0052] Traditional ultra-thin overlays or micro-surfacing treatments primarily rely on the physical adsorption and mechanical interlocking of the waterproof layer to achieve interlayer bonding, which is susceptible to water damage and delamination. This invention, however, utilizes water-based epoxy resin to form a three-dimensional cross-linked network penetrating the waterproof bonding layer and the high-slip-resistance thin layer after demulsification and curing. This creates a strong chemical bond between the two layers, significantly improving interlayer bonding strength and overall durability. Furthermore, conventional curing layers often employ continuous gradation to achieve a dense structure, with their anti-slip performance dependent on the micro-texture of the aggregates. This invention innovatively uses single-size wear-resistant aggregates, partially embedded and protruding from the surface of the water-based epoxy emulsified asphalt binder in a point-contact manner. This actively constructs a uniform and stable macroscopic structural depth, transforming the anti-slip mechanism from relying on material surface properties to being dominated by the macroscopic structure. This fundamentally solves the problem of synergistically improving anti-slip performance and durability.

[0053] Comparative Example 1 This comparative example uses ordinary cationic emulsified asphalt (without added water-based epoxy resin) as the waterproof bonding layer (spraying rate 0.8 kg / m²), and the surface layer uses standard MS-3 type continuous gradation micro-surfacing. The aggregate is diabase. Testing showed that the interlayer bond strength was only 0.4-0.6 MPa, the rut width variation rate of the mixture reached 5.2%, and the wet tire abrasion value after 6 days of immersion in water was 700-800 g / m². 2The construction depth (TD) is approximately 0.6-0.8 mm. This is consistent with the present invention (interlayer bond strength ≥ 1.5 MPa, mixture TD ≥ 1.2 mm, rut width variation rate ≤ 2%, wet wheel abrasion value ≤ 300 g / m after 6 days of immersion in water). 2 Compared to the control group, the control group has significantly weaker interlayer adhesion, resistance to deformation and water damage due to the lack of chemical bonding, and its dense gradation results in insufficient macroscopic anti-slip structure.

[0054] Comparative Example 2 This comparative simulation of a simplified chip seal process involves spreading SBR modified emulsified asphalt (1.0 kg / m²) on the existing road surface, followed by direct application of 3-5 mm single-size basalt aggregate. The initial texture depth can reach 1.0 mm, but the interlayer bond strength is extremely low (<0.3 MPa), and the aggregate retention rate (wet wheel abrasion value) after 1 hour of immersion in water is as high as 800-1000 g / m². In contrast, this invention (interlayer bond strength ≥1.5 MPa, sand adhering to the load wheel ≤200 g / m² after 1 hour of immersion in water) demonstrates this. 2 This comparative example lacks an integral bonding layer and interlocking binder, resulting in easily loose aggregates and extremely poor durability.

[0055] Comparative Example 3 High-content SBS modified emulsified asphalt binder layer + single-size surface layer This comparative example used high-performance SBS-modified emulsified asphalt (SBS content ≥5%) as the binder layer, and the surface layer attempted to mimic the use of single-size diabase aggregate in this invention. The results showed that its interlayer bond strength was approximately 0.8-1.0 MPa, superior to Comparative Example 1 but still significantly lower than Example 1 of this invention (≥1.5 MPa), and its wet wheel abrasion value after 1 hour of immersion in water was 300-400 g / m². 2 The wet wheel wear value after 6 days of immersion in water is 400~500g / m. 2 Compared with the present invention (the amount of sand adhering to the load wheel after immersion in water for 1 hour is ≤200g / m), 2 The wet wear value of the wheel after 6 days of immersion in water is ≤300g / m. 2 In this comparative example, the binder lacked chemical bonding, resulting in weak adhesion to the aggregate. This also indicates that even with the use of high-performance polymers, the physical modification inherently cannot achieve the effect of the three-dimensional cross-linked network of waterborne epoxy resin in terms of long-term durability and interlayer chemical bonding strength.

[0056] Comparative Example 4 This comparative example uses the water-based epoxy emulsified asphalt of this invention as the waterproof bonding layer, but the surface layer uses AC-10 continuously graded hot-mix asphalt mixture (2 cm thick). Test results show that although the interlayer bond strength can reach 1.3 MPa, proving the effectiveness of the epoxy system, the texture depth (TD) of the surface layer is only 0.6-0.8 mm, and the pendulum value (BPN) is approximately 60-65. This contrasts sharply with the present invention (TD≥1.2 mm, BPN≥75), demonstrating that the contribution of a single-particle-size point contact structure to improving macroscopic anti-skid performance is far superior to that of a continuously graded dense structure.

[0057] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A water-based epoxy emulsified asphalt high skid-resistance thin-layer structure, characterized in that, The high anti-slip thin-layer structure includes, from bottom to top: Waterborne epoxy emulsified asphalt waterproof bonding layer is formed by mixing emulsified asphalt and waterborne epoxy resin and then demulsifying and curing it. It is used to seal the original asphalt pavement and provide interlayer bonding. A waterborne epoxy emulsified asphalt high anti-skid thin layer is formed by mixing, spreading, rolling and curing abrasion-resistant aggregate and waterborne epoxy emulsified asphalt binder. The waterborne epoxy emulsified asphalt binder is made by mixing emulsified asphalt and waterborne epoxy resin. After demulsification and curing, it forms a three-dimensional cross-linked network structure. The abrasion-resistant aggregate is embedded in the waterborne epoxy emulsified asphalt binder in a point contact form and partially protrudes from the surface of the waterborne epoxy emulsified asphalt binder, together forming a waterborne epoxy emulsified asphalt high anti-skid thin layer with macroscopic structural depth. The waterborne epoxy emulsified asphalt waterproof adhesive layer and the waterborne epoxy emulsified asphalt high anti-skid thin layer are chemically bonded through a three-dimensional cross-linking network of epoxy resin.

2. The water-based epoxy emulsified asphalt high skid-resistance thin-layer structure according to claim 1, characterized in that, The waterborne epoxy emulsified asphalt waterproof adhesive layer comprises the following components in the following mass ratio: 100 parts emulsified asphalt and 3-6 parts waterborne epoxy resin. The emulsified asphalt used is a cationic slow-cracking emulsified asphalt with a solid content of 50% to 60%. The waterborne epoxy resin is a two-component epoxy resin, wherein component A is an epoxy emulsion and component B is a curing agent.

3. The water-based epoxy emulsified asphalt high skid-resistance thin-layer structure according to claim 1, characterized in that, The water-based epoxy emulsified asphalt high anti-skid thin layer comprises the following components in the following mass ratio: 100 parts of high anti-skid aggregate with a single particle size of 3mm~5mm, 10~14 parts of water-based epoxy emulsified asphalt binder, 1~3 parts of cement admixture, and 2~6 parts of water for wetting and adjusting consistency.

4. The water-based epoxy emulsified asphalt high anti-skid thin-layer structure according to claim 1, characterized in that, The application rate of the water-based epoxy emulsified asphalt waterproof adhesive layer is 0.6~0.8 kg / m³. 2 ; The thickness of the water-based epoxy emulsified asphalt high anti-skid thin layer is 5mm~12mm.

5. The water-based epoxy emulsified asphalt high anti-skid thin-layer structure according to claim 3, characterized in that, The waterborne epoxy emulsified asphalt high anti-skid thin layer comprises the following components in the following mass ratio: 100 parts emulsified asphalt and 6-30 parts waterborne epoxy resin. The emulsified asphalt is a cationic slow-cracking emulsified asphalt with a solid content of not less than 60%. The waterborne epoxy resin is a two-component epoxy resin, wherein component A is an epoxy emulsion and component B is a curing agent; The cement admixture is P.O42.5, and the water used for wetting and consistency adjustment is tap water.

6. The water-based epoxy emulsified asphalt high skid-resistance thin-layer structure according to claim 1, characterized in that, The wear-resistant aggregates include basalt, diabase, steel slag, and ceramsite with a single particle size range of 3-5 mm.

7. A construction method for a water-based epoxy emulsified asphalt high skid-resistance thin-layer structure as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Clean and dry the original asphalt pavement, and treat potholes, craters, and cracks larger than 5mm. S2. Mix the two-component waterborne epoxy resin in proportion and add it into the emulsified asphalt tank of the sprayer. Turn on the internal circulation to make the components evenly mixed. Then spray it onto the treated road surface in a controlled amount to form a waterborne epoxy emulsified asphalt waterproof bonding layer. S3. Waterborne epoxy resin and emulsified asphalt are premixed in a slurry sealer to form a binder, which is then mixed with single-size wear-resistant aggregate, cement, and water, and then spread on the waterborne epoxy emulsified asphalt waterproof bonding layer. S4. After the binder in the paving layer in S3 has broken emulsion and formed initial bond strength, the thin layer is rolled by static pressure to make the aggregate stably embedded in the binder and form a uniform surface. S5. After the thin layer in S4 has been rolled, it is sealed and cured. Traffic is opened after the water-based epoxy resin has fully cured to form a three-dimensional cross-linked network structure and the strength meets the requirements.

8. The construction method of a water-based epoxy emulsified asphalt high skid-resistance thin-layer structure according to claim 7, characterized in that, In S2 and S3, the mixing of waterborne epoxy resin and emulsified asphalt is achieved by opening the internal circulation in the tank of the construction machinery for at least 10 minutes, the speed of the sprayer is controlled at 2-4 km / h, and the speed of the paver is controlled at 1.5-3.0 km / h.

9. The construction method of a water-based epoxy emulsified asphalt high skid-resistance thin-layer structure according to claim 7, characterized in that, In S4, when the temperature is between 5-25℃, the compaction time is 3-4 hours; When the temperature is above 25℃, the compaction time is 1-2 hours; During the compaction process, a double-drum roller with a capacity of no more than 13 tons is used to perform 1-2 static compactions at a speed of 2-4 km / h.

10. The construction method of a water-based epoxy emulsified asphalt high skid-resistance thin-layer structure according to claim 7, characterized in that, In S5, the curing time is determined based on the ambient temperature to ensure that the waterborne epoxy resin is fully cross-linked and cured to achieve the design strength. When the temperature is between 5-25℃, the health regimen should last for 2-3 hours. When the temperature is above 25℃, the health regimen should last for 1-2 hours.

Citation Information

Patent Citations

  • High-performance waterborne epoxy modified emulsified asphalt micro-surfacing material and preparation method thereof

    CN114644493A

  • Method for determining effective construction time of mixing type waterborne epoxy emulsified asphalt

    CN116399756A

  • Gravel-embedded structure between ultra-high performance concrete surface and upper surface layer and construction method

    CN107059529A

  • High-skid-resistance wear-resistant surface layer and construction method thereof

    CN114182597A

  • Multi-point contact type thin-layer noise reduction rubber modified asphalt concrete overlay structure and preparation method thereof

    CN115787388A

Cited By

  • Stress luminescence type chemical anchoring fog sealing layer material with blackening and wear-resisting functions and construction method of stress luminescence type chemical anchoring fog sealing layer material

    CN121573931A